Lamp and terracotta figurine production in the Roman Period at Tarsus-Gözlükule (Turkey) - Mondin, Cristina; Maranzana , Paolo (Rei Cretariae Romanae Fautorum Acta, 2024)
This article aims to discuss the recent archaeological evidence for pottery production from the Roman period discovered at Tarsus-Gözlükule. 70 years after the publication of H. Goldman’s seminal study of pottery at this site, excavations conducted by teams led by Prof. Özyar (Bögazici University) revealed the presence of a multi-layered production site on the Gözlükule mound; here, investigations revealed two levels of kilns, a clay processing basin, and a work surface made of production waste dated to the Roman Period. The workshop is small, and it was mainly employed to produce lamps (categorised as groups XVI and XVIII in Goldman’s publication) and votive objects. This preliminary presentation of the results of the archaeological research gives an overview of the production and the site dated to the 2nd-3rd centuries AD, which is still being studied and excavated.